Números complexos: um pouco de história, ensino e aplicações - Costa, Antônio Geraldo Lacerda da (2013)
We present the main properties related to complex numbers. We justify as the history of mathematics can contribute to learning that content. Then we describe briefly the history of complex numbers. We also show where the complex numbers can be applied both within mathematics itself, and beyond.